2000
DOI: 10.1074/jbc.m005073200
|View full text |Cite
|
Sign up to set email alerts
|

1-Cys Peroxiredoxin, a Bifunctional Enzyme with Glutathione Peroxidase and Phospholipase A2 Activities

Abstract: This report provides definitive evidence that the protein 1-Cys peroxiredoxin is a bifunctional ("moonlighting") enzyme with two distinct active sites. We have previously shown that human, rat, and bovine lungs contain an acidic Ca 2؉ -independent phospholipase A 2 (aiPLA 2 ). The cDNA encoding aiPLA 2 was found to be identical to that of a non-selenium glutathione peroxidase (NSGPx). Protein expressed using a previously reported E. coli construct which has a His-tag and 50 additional amino acids at the NH 2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
306
1
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(328 citation statements)
references
References 26 publications
14
306
1
7
Order By: Relevance
“…Another possibility is that in the absence of a GPX, other antioxidant enzyme(s) are upregulated in vivo to compensate for the lack of Gpx activity. For example, in S. cerevisiae, 1-Cys peroxiredoxins have been shown to possess glutathione peroxidase activity (Chen et al, 2000). In addition, it has been reported that glutaredoxins, which are small glutathione-dependent oxidoreductases, can act as glutathione peroxidases and reduce peroxides in S. cerevisiae (Collinson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that in the absence of a GPX, other antioxidant enzyme(s) are upregulated in vivo to compensate for the lack of Gpx activity. For example, in S. cerevisiae, 1-Cys peroxiredoxins have been shown to possess glutathione peroxidase activity (Chen et al, 2000). In addition, it has been reported that glutaredoxins, which are small glutathione-dependent oxidoreductases, can act as glutathione peroxidases and reduce peroxides in S. cerevisiae (Collinson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Interestingly, only Prx6 uses glutathione as a physiological reductant, while other Prxs use thioredoxin. 16 Then, how does Prx6 regulate TRAIL-mediated cell death through DED caspases? The antiapoptotic activity of Prx6 can be exerted mainly by two possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Prx6 is the only member of 1-Cys Prx and has non-selenium glutathione peroxidase and phospholipase A 2 activities. 16 Upregulation of Prx6 suppresses intracellular enzyme inactivation, membrane phospholipid peroxidation, and cell death mediated by oxidative stress. 17,18 In addition, Prx6-deficient mice are susceptible to oxidative stress by hypoxia or paraquat treatment, leading to increase of mortality and lung injury.…”
mentioning
confidence: 99%
“…Expression of the C47S Prdx6 mutant partially rescued (ϳ50%) both the agonist-induced PLA 2 activity and ROS generation (Table 4). On the other hand, there was no significant rescue of either PLA 2 activity or ROS generation in endothelial cells transfected with constructs that express S32A, H26A, or D140A mutant Prdx6; these 3 amino acids constitute the Prdx6 PLA 2 catalytic triad, and each is necessary for PLA 2 activity but not for H 2 O 2 peroxidase activity (21,22). These results for "rescue" show that the PLA 2 activity of Prdx6 is required for Ang II-mediated activation of NOX2 in mouse PMVEC.…”
Section: Ros Production With Ang II Treatment Of Lung Endothelium In mentioning
confidence: 99%